Implementing remote supervision to improve HIV service delivery in rural Malawi - Steven Masiano; Shalom Dunga; Tapiwa Tembo; Colin Pfaff; Carrie Cox; Beston Robert; Saeed Ahmed; Maria Kim (Journal of Global Health Reports)
# Background Viral load (VL) testing is critical to monitor response to ART and optimize HIV treatment and care outcomes. Unfortunately, VL testing coverage remains suboptimal in much of sub-Saharan Africa. With the COVID-19 pandemic significantly curtailing in-person supervision of HIV services delivery, low-cost and scalable ways of conducting remote supervision are needed. We evaluated the effects of remote supervision utilizing the WhatsApp platform, a form of supervision highly applicable in the times of COVID-19, on VL testing coverage in rural Malawi.